Rhetorical Construction of West Africain Travels In West Africa - Rana Bhat, Shuv Raj (Tribhuvan University Journal, 2016)
Viewed from David Spurr’s lenses developed in “The Rhetoric of Empire,” Mary Kingsley produces knowledge of West Africa and establishes a claim over her in her travelogue Travels in West Africa. Through the deployment of surveillance, appropriation, debasement and negation, she draws an ambivalent picture of Africa: one associated with filth, defilement, danger, darkness and death and the other endowed with natural vegetation and resources. Both sides of the picture call for the arrival of the British to improve the lifestyle of the Africans and to utilize the natural resources.